Giant Cell Tumor of the Proximal Phalanx: Report of two Cases Treated by Two Different Methods and Review of the Literature - Demiroz, S; Yildirim, A. N. T; Akan, M; Faruq, A. U; Ibrahim, U. A; Ozkan, K (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2022)
The hand is an extremely rare site for giant cell tumor (GCT). There are only a few reported cases of GCT including the hand, and even fewer reporting involvement of phalanges. GCTs in small bones are typically more aggressive and have higher local recurrence and rate of metastasis in younger patients compared to long bone involvement, so the treatment is more clinically challenging in the hand. In this study, we present the management of giant cell tumors of the proximal phalanxin two patients treated with two different method; ray resection and arthrodesis using an iliac crest graft. Key words: giant cell tumor, phalanx, hand, recurrence.
Keywords: nádory kostí; Hand; ruka; Finger Phalanges; lidé; artrodéza; obrovskobuněčný nádor kosti; Bone Neoplasms; Arthrodesis; Humans; kosti prstů ruky; Giant Cell Tumor of Bone